In silico Study of Pharmacological Treatments against SARS-CoV2 Main Protease - Youness Kadil (Journal of Pure and Applied Microbiology, 2020)
The COVID-19 caused by a new type of coronavirus has emerged from China and led to thousands of death globally. Despite the efforts engaged in studying this newly emerged virus and searching for its treatment, the understanding of the COVID-19 drug and target protein interactions still represent a key challenge. Several molecules have demonstrated In-Vitro activity against the SARS-CoV-2 virus and/ or potential clinical benefit in observational and non-randomized studies. Randomized clinical trials of an appropriate size are currently ongoing to establish the efficacy of these therapeutic proposals. Herein, concerning these diverse guidelines and therapeutic suggestions of different approaches to the treatment, this research aims to provide a molecular analysis of the interaction between the principal molecules cited in bibliography and the active protease site of the virus.